Android Based Differentiated Science Media for Elementary Literacy Improvement: Media Sains Berdiferensiasi Berbasis Android untuk Literasi Sekolah Dasar - Bumantara, Bayu; Masjid, Akbar Al; Khosiyono, Banun Havifah Cahyo; Djufri, Elyas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Scientific literacy in elementary education is increasingly essential in response to technological development and digital learning environments. Specific Background: Science learning in elementary schools remains dominated by teacher-centered methods, resulting in abstract conceptual understanding that does not align with students’ concrete cognitive development stages, particularly in Earth and Moon motion topics. Knowledge Gap: Although Android-based learning media have been widely developed for science education, differentiated science media specifically designed for Earth and Moon movement materials at the elementary level remain limited. Aims: This study aimed to develop, validate, and test Android-based differentiated science learning media designed to support elementary students’ literacy skills. Results: The developed media demonstrated high feasibility, with material validity reaching 87%, media feasibility 75%, and practitioner practicality between 95–96%. Trial results showed significant improvements between pretest and posttest scores, supported by moderate N-Gain values ranging from 0.64 to 0.67 and statistically significant paired sample test results. Novelty: This study presents differentiated Android-based science media integrating visual, auditory, and kinesthetic learning modes for abstract Earth and Moon motion concepts. Implications: The findings indicate that differentiated digital science media can support concrete understanding, promote independent learning, and provide practical instructional alternatives for elementary science classrooms. Highlights • The learning media integrates differentiated visual, auditory, and kinesthetic components aligned with student learning styles• Validation results confirm high feasibility and practical classroom applicability• Trial outcomes show consistent improvement in student literacy achievement Keywords Android Learning Media; Differentiated Learning; Science Literacy; Elementary Education; Digital Learning Media